Professional Liability - Zana, Mario (2005)
This article analyzes the civil liability of the professional and the way in which Italian doctrine and jurisprudence regulate this situation. It is pointed out that the professional activity must be evaluated considering the diligence –of the good father of the family as a general and objective criterion– and the technical expertise of the professional, adapted to the nature of the expected service and the circumstances of each particular case. To that extent, it is important to distinguish between obligations that guarantee a specific result (result obligations) and those in which only technical diligence is required (means obligations), as well as the need for a rigorous assessment of technical competence in situations of particular difficulty. In this regard, there is an evolution in the line of case law by making the rigid distinction between obligations of means and of results more flexible, transferring the burden of proof to the professional to demonstrate his diligence in the face of abnormal negative results that may presume the inadequate or negligent execution of the professional service.